PENGARUH NARSISME DAN JOB STRESSOR PADA PERILAKU KERJA KONTRA PRODUKTIF DENGAN RESPON EMOSIONAL NEGATIF (ANGER) SEBAGAI MEDIATOR - Hariyanti Nugraheni; Salamah Wahyuni (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2016)
This research aimed to analyze the effect of narcissism on counterproductive behavior, narcissism on anger/negative emotion; the effect of job stressor on anger/negative emotion; the effect of anger/negative emotion on counterproductive working behavior; and anger/negative emotion mediating the effect of narcissism and job stressor on counterproductive working behavior. The sample of research was the employees in PT. Bank Mandiri (Persero) Tbk of Solo areas consisting of 200 respondents. The method of sampling used was non probability sampling, judgment sampling. Meanwhile the method of analyzing data used was Structural Equation Model (SEM).The result of hypothesis testing showed that narcissism affected positively and significantly the counterproductive working behavior; narcissism affected positively and significantly on anger/negative emotion; job stressor affected significantly the anger/negative emotion; anger/negative emotion affected significantly and positively the anger/negative emotion and significantly mediated the effect of narcissism and job stressor in counterproductive working behavior.